PEMIKIRAN PENDIDIKAN ISLAM K.H. MUHAMMAD ZAINI ABDUL GHANI (STUDI PENDIDIKAN AKHLAK DI MARTAPURA, KALIMANTAN SELATAN) - Ali matur raiyah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2019)
Abstract: This study uses qualitative method using biography approach which means the study of an individual by explaining the results of K.H Muhammad Zaini Abdul Ghani's thoughts. Research findings about Islamic education thought. K. H. Muhammad Zaini Abdul Ghani include the purpose of Islamic education which means to really know Allah SWT, so always remembering Him in every situation. Then, educators mean people who change students to be better, the curriculum which is used related with experience outside of school as part of educational activities. Then the method used by K.H. Muhammad Zaini Abdul Ghani is an exemplary method, habituation, *bandongan*, demonstration, and question and answer method. While the works of KH. Muhammad Zaini Abdul Ghani included Risalah al-Mubarakah, Manakib asy-syeikh Muhammad Samman al-Madani, Ar-risalat an nuraniyah fi syarh at-tawassulat as-sammaniyah, Nubzat min manaqib al imam al-masyhur bil ustadz al a ' zham Muhammad bin ali ba'alawi, Al-amdad fi Aurad Ahl Al-Widad, Manaqib Ash-Shaykh As-Sayyid Muhammad bin Abdul Qadir Al-Qadiri and Al-Fushul Al-Ilmiyah wa Al-Ushul Al-Hikamiyah. Keywords: Thought, Islamic Education, K.H. Muhammad Zaini Abdul Ghani.